(untitled) (International Journal of Advanced Research in Computer Science, 2017)
OFDM has been adopted as a standard for various high data rate wireless communication systems due to several benefits. One of the major drawbacks in OFDM system is its high Peak-to-Average Power Ratio (PAPR) of its transmitted signals thereby making transmitter amplifier to operate beyond its linear range of operation resulting in signal distortion. In this research work a simple method for reducing Peak-to-Average Power Ratio in OFDM is presented. The method is based on Discrete Cosine Transform (DCT) aided successive addition and subtraction (SAS) of data symbols within a single OFDM frame. Performance of the proposed method is evaluated and compared with the existing techniques. Joint reduction in PAPR by combining SAS preprocessed DCT technique and companding is also presented where system utilizes companding technique to further reduce the PAPR of the OFDM signal. Keywords: OFDM; PAPR; DCT; SAS; CompandingOFDM has been adopted as a standard for various high data rate wireless communication systems due to several benefits. One of the major drawbacks in OFDM system is its high Peak-to-Average Power Ratio (PAPR) of its transmitted signals thereby making transmitter amplifier to operate beyond its linear range of operation resulting in signal distortion. In this research work a simple method for reducing Peak-to-Average Power Ratio in OFDM is presented. The method is based on Discrete Cosine Transform (DCT) aided successive addition and subtraction (SAS) of data symbols within a single OFDM frame. Performance of the proposed method is evaluated and compared with the existing techniques. Joint reduction in PAPR by combining SAS preprocessed DCT technique and companding is also presented where system utilizes companding technique to further reduce the PAPR of the OFDM signal. Keywords: OFDM; PAPR; DCT; SAS; Companding